Febri dwi laksana, Evaluasi Program Jamianan Kesehatan Indonesia (Studi Kasus Penanganan Covid 19 di Indonesia) - laksana, @febri (Afiasi : Jurnal Kesehatan Masyarakat, 2020)
World health organization, WHO, guarantees that every community in the world gets a good standard of health services. Through Universal Health Coverage, it is hoped that countries around the world are able to raise the level of health services that have so far been overlooked. This is done as an effort to guarantee human rights that guarantee rights freedom of life and the right to health services. But the health standard system (UHC) is still lacking in its application in Indonesia. This is seen from several important points that occur in Indonesia. Hospital facilities are still inadequate, especially hospitals in the region. In this paper I will provide information regarding evaluations carried out on the health insurance program in Indonesia with case studies of how to deal with Covid 19 in Indonesia whether it is in accordance with health standards or not.